(untitled) (Journal of Engineering, 2006)
Active control strategy had been used for controlling the vibration response, with considering the simplification in the design and keep away from complexity and high cost in order to extend the actual application of the active control systems. The control program is responsible for identifying the acquired data and make comparisons and decisions required for increase or decrease the actuator stiffness, by instructing the control signal to open the inlet or the exhaust valve respectively. The PC sound card has been used as a Data Acquisition Card. The proposed control strategy had been simulated and tested to control the vibration response of a single degree of freedom spring-mass-damper system excited harmonically at a fixed frequency and with variations of different system parameters (mass, damping constant, and excitation force). Two testing cases are used to investigate the ability of using the proposed actuator and the control strategy in the vibration control field.